TUBERCULOSIS INFECTION ON DYSFUNCTIONAL FARMS - Masharipova Sh. S.; Masharipov S.M. (European Science Publishing, 2024)
In 2022, tuberculosis claimed the lives of a total of 1.3 million people (including 167,000 people infected with HIV). Worldwide, tuberculosis is the second leading cause of death from infectious diseases after COVID-19 (mortality rates are higher than from HIV infection and AIDS). The urgency of the problem of tuberculosis incidence is associated with the spread of drug-resistant strains of the causative agent of tuberculosis, high susceptibility to the disease of unvaccinated persons, possible chronization of the process with late medical treatment and refusal of etiotropic treatment. It is known that sick animals and small cattle cause human tuberculosis infection. The symptoms of tuberculosis in livestock have not been sufficiently studied in the literature, which significantly complicates the clinical recognition of tuberculosis in animals. There are no effective methods of diagnosis and specific prevention of the disease.
Keywords: Mantoux test, BCG vaccination, epidemic, focus of infection, epizootic, temperature, causative agent of tuberculosis, population, pets.